Rôle de la créative kinase myofibrillaire dans la contraction cardiaque : Etude des propriétés mécaniques des fibres cardiaques pelées - Mekhfi, Hassane (Rôle de la créative kinase myofibrillaire dans la contraction cardiaque : Etude des propriétés mécaniques des fibres cardiaques pelées, 1988)
The role of myofibrillar creatine kinase (MM-CK) studied in rat cardiac skinned fibres whose membranes were solubilized with Triton X100. Force-Ca⁺⁺ relationship shows that the Ca⁺⁺ sensitivity of contraction was altered by substrates and products of both the myonsin-ATPase (M-ATPase) and the MM-CK such as inorganic phosphate (Pi), phosphocreatine (PCr) and ADP. However, neither ischemia nor hypertrophy modified this parameter. These studies show that the Ca⁺⁺ sensitivity of contraction is also dependent on the rate of actomyosin bridges cycling. Transient tension rate responses to quick stretches were used to study the kinetics of actomyosin bridges. Changes in Pi, PCr and ADP concentrations modified these kinetics. Tension responses were also slowed in muscles from rat hearts made hypertrophic by pressure overload. This result is in agreement with myosin isoenzymic pattern. Rigor tension was studied as a fuction of MgATP concentration. The addition of PCr facilitates relaxation of rigor tension induced by MgATP. This facilitation (i.e., MM-CK efficacy) was altered by Pi but not by hypertrophy, or irreversible ischemia. These results show the role of creatine kinase in the contraction and suggest a functionnal coupling between M-ATPase and MM-CK. Moreover, the efficacy of myofibrillar creatine kinase is preserved during compensatory hypertrophy and accute ischemia.
Keywords: Créatine kinase; Myofibrillaire; Contraction cardiaque; Propriété mécanique; Fibre cardiaque pelée